2007
DOI: 10.1080/00218460701198644
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Bioadhesivity of Osteoblast Cells on Titanium Alloy Surface Modified by Nd:YAG Laser

Abstract: The surface microtopography and physical-chemical results of Ti6Al4V alloy were investigated in relation to bone cell response. Nd:YAG-laser-treated surfaces with (1.06 lm wavelength, 200 ls pulse duration, and a fluence of 140 Jcm À2 exhibited an improved hydrophilic behavior due to a lower contact angle compared with the control sample. Cell spreading on the implanted specimens was analyzed by scanning electron microscope (SEM), and their condition in a specific area was studied for 10 cells from three separ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
2
4
0
Order By: Relevance
“…From micro-mechanical point of view, the previous finding of enhanced properties [16,20,22] after laser treatment at 140 Jcm -2 compared to untreated, as well as 70 and 250 Jcm -2 samples, were consistent with new finding of significant difference between samples' surface morphologies. The higher surface hardness (850, 377 HVN for 140 Jcm -2 and untreated samples, respectively), enhanced corrosion resistance, lower contact angle (35°for 140 Jcm -2 and 70°for untreated sample) and higher surface tension (60 mNm -1 ) for 140 Jcm -2 compared to untreated surface (39 mNm -1 ) have been reported before.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…From micro-mechanical point of view, the previous finding of enhanced properties [16,20,22] after laser treatment at 140 Jcm -2 compared to untreated, as well as 70 and 250 Jcm -2 samples, were consistent with new finding of significant difference between samples' surface morphologies. The higher surface hardness (850, 377 HVN for 140 Jcm -2 and untreated samples, respectively), enhanced corrosion resistance, lower contact angle (35°for 140 Jcm -2 and 70°for untreated sample) and higher surface tension (60 mNm -1 ) for 140 Jcm -2 compared to untreated surface (39 mNm -1 ) have been reported before.…”
Section: Discussionsupporting
confidence: 85%
“…From osseointegration point of view, the observation of change in density of cell network from mono-layer to multi-layer for 140 Jcm -2 samples [20,22] were consistent with the optimum height profile obtained in the sample (Figs. 2, 3).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Therefore, it is used as filler in small bone defects and as a coating on metal implants such as titanium (Bai et al 2010a; Sadat-Shojai et al 2010; Sato et al 2006). Recent studies have reported improved ossification process and implant fixation through various methods including plasma spray and laser (Roy et al 2011; Topić et al 2006; Khosroshahi et al 2009, 2007). …”
Section: Introductionmentioning
confidence: 99%